2019
DOI: 10.1242/dev.172700
|View full text |Cite
|
Sign up to set email alerts
|

Novel functions of the ubiquitin-independent proteasome system in regulatingXenopusgermline development

Abstract: In most species, early germline development occurs in the absence of transcription with germline determinants subject to complex translational and post-translational regulations. Here, we report for the first time that early germline development is influenced by dynamic regulation of the proteasome system, previously thought to be ubiquitously expressed and to serve 'housekeeping' roles in controlling protein homeostasis. We show that proteasomes are present in a gradient with the highest levels in the animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Immunofluorescence (IF) clearly indicates enrichment of the 20S CP in the animal hemisphere of 8-cell stage embryos, consistent with recent IF findings in fertilized eggs (Hwang et al). 32 Asymmetric distribution of the proteasome during the oocyte to embryo transition in Xenopus may allow stabilization of vegetally localized proteins that are critical for germ cell development (Hwang et al). 32 Furthermore, the protein DDX4/Vasa (also known as Xenopus vasa-like gene 1) was localized to the vegetal hemisphere of the embryo (indicated in yellow in Figure 4A), in line with previous findings by Sindelka et.al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunofluorescence (IF) clearly indicates enrichment of the 20S CP in the animal hemisphere of 8-cell stage embryos, consistent with recent IF findings in fertilized eggs (Hwang et al). 32 Asymmetric distribution of the proteasome during the oocyte to embryo transition in Xenopus may allow stabilization of vegetally localized proteins that are critical for germ cell development (Hwang et al). 32 Furthermore, the protein DDX4/Vasa (also known as Xenopus vasa-like gene 1) was localized to the vegetal hemisphere of the embryo (indicated in yellow in Figure 4A), in line with previous findings by Sindelka et.al.…”
Section: Resultsmentioning
confidence: 99%
“…32 Asymmetric distribution of the proteasome during the oocyte to embryo transition in Xenopus may allow stabilization of vegetally localized proteins that are critical for germ cell development (Hwang et al). 32 Furthermore, the protein DDX4/Vasa (also known as Xenopus vasa-like gene 1) was localized to the vegetal hemisphere of the embryo (indicated in yellow in Figure 4A), in line with previous findings by Sindelka et.al. 50 DDX4/Vasa belongs to the family of DEAD-box RNA helicases and is a marker for germ cell specification in diverse animal species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31][32][33][34] We have recently discovered a potent 21 amino-acid degradation sequence within Xenopus laevis Dnd protein that promotes rapid ubiquitin-independent proteasomal degradation of Dnd in Xenopus oocytes and mammalian cell lines such as HEK293T and GC-2spd. 35 To determine whether this degradation sequence (here referred to as degron or deg) can be used as a general moiety to mediate degradation of intracellular proteins, we fused tandem arrays of degrons to the C-terminus of firefly luciferase (FLuc) protein (FLuc-tevS-Ndeg, N = 1, 2, and 3). A tobacco etch virus (TEV) protease recognition site (tevS) was sandwiched between FLuc and degron to render TEV-mediated rescue of protein degradation (Figure 1a).…”
Section: Degron-directed Constitutive Degradation Lowers Target Protementioning
confidence: 99%
“…[42][43][44][45] We previously reported that degradation mediated by the Dnd degron was blocked only when all three types of the ubiquitin-independent proteasome were inhibited simultaneously. 35 Ubiquitin-independent proteasomes are widely present in the majority of cell types. Thus, different from the majority of degrons, which are often recognized by tissue-specific E3 ubiquitin ligases, the Dnd degron can keep the protein of interest at a very low expression level in a wide variety of cells.…”
Section: Stabilization Of Ca Mek Via Glimpse Enables Optogenetic Uprementioning
confidence: 99%